Analisis Komunikasi Antarbudaya dalam Pembentukan Beragama di Masyarakat Multikultural - Assyifa, Widya Nur; Aprilliyanti, Putri Hani; Dwi Putri, Shabrina Nadiya; Mulyadi, Budi; Kurniawan, Vebri (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
Intercultural communication and religious tolerance are topics of increasing importance in the context of modern globalization which demands more intense interaction between individuals from different cultural backgrounds. This abstract explores the relationship between intercultural communication and religious tolerance by integrating findings from various empirical and theoretical studies over the last period. Research shows that positive interactions between individuals from different cultural groups can reduce stereotypes, increase mutual understanding, and strengthen social integration. TheoDries such as social contact theory and social identity theory provide relevant conceptual frameworks in understanding the dynamics of effective intercultural communication and its impact on religious tolerance